Wisconsin healthcare utilization cost among American Indians/Alaskan Natives with and without ADRD. (31st December 2021) - Johnson, Adrienne L; Norton, Derek L; Mundt, Marlon P; Seep, Elaina; Wyman, Mary F; James, Taryn T; Zuelsdorff, Megan; Lambrou, Nickolas H; Umucu, Emre; Gleason, Carey E
Abstract: Background: The annual cost of Alzheimer's disease and related dementias (ADRD) in the US is 355 billion; that rate is expected to triple by 2050. Individuals ADRD accrue higher healthcare utilization costs than peers without ADRD, including those with comorbid conditions (e.g., cancer, coronary artery disease, diabetes). Although research examining prevalence of ADRD in American Indians/Alaskan Natives (AI/AN) is limited, recent data suggest the prevalence of ADRD in the AI/AN population is 49% higher than in the Non‐Hispanic White population. Only one study has evaluated the healthcare utilization of AI/ANs, which showed greater utilization rates among those with (versus without) ADRD diagnosis and a rapid increase in utilization following ADRD diagnosis. We have yet to comprehensively analyze the additive cost of ADRD within the US among AI/ANs. Method: Post‐paid electronic health record data from Wisconsin Department of Health Services were retrospectively analyzed to compare non‐Tribal and Indian Health Service utilization costs among Medicaid enrolled AI/ANs, ages 40 and older, based on the presence or absence of ADRD throughout data review (7/1/2015 through 7/1/2020). Three separate analyses were completed, separated by payer programs: fee‐for‐service, HMO, and long‐term care. In each analysis, controls (individuals without ADRD) were matched to cases (individuals with ADRD) using exact matching across the subclasses defined by crossings of age group, sex, diabetes status, and emphysema status (Tables 1‐3). Weighted Wilcoxon rank sum tests were then used to compare total payable costs per capita. Tests accounted for both the subclass sampling strata and weights produced through the matching process. Weighted Chi‐square tests of association were also employed to confirm balance was achieved across age groups, sex, diabetes status, and emphysema status in the matching process; no weighted imbalances occurred. Result: Among all three programs, AI/ANs with dementia had significantly higher healthcare utilization costs than those without dementia, after matching for age, gender, diabetes and emphysema status. Conclusion: AI/ANs with ADRD accrued at 25, 000 more over 5 years, on average, compared to those without ADRD. The greatest cost disparity was in long‐term care waiver programs (50, 879). Cost‐effective interventions aimed at ADRD prevention and treatment among AI/ANs are greatly needed.